2018
DOI: 10.1017/s1368980017004232
|View full text |Cite
|
Sign up to set email alerts
|

Randomized control trials demonstrate that nutrition-sensitive social protection interventions increase the use of multiple-micronutrient powders and iron supplements in rural pre-school Bangladeshi children

Abstract: ObjectiveTo examine the impact of a nutrition-sensitive social protection intervention on mothers’ knowledge of Fe deficiency, awareness of multiple-micronutrient powders (MMP) and the consumption of MMP and other Fe supplements by their children aged 6–59 months.DesignTwo randomized controlled trials with treatment arms including cash transfers, food transfers, cash and food transfers, cash and nutrition behaviour change communication (BCC), and food and nutrition BCC were implemented over two years. Both inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…In the case of the trials ( 7 ) conducted in the study published in a recent issue of Public Health Nutrition ( PHN ), the results showed that cash conditional on nutrition behaviour change communication (‘Cash + BCC’) yielded higher impacts in terms of knowledge of Fe deficiency, awareness of multiple-micronutrient powders (MMP) and reported consumption thereof for children aged 6–59 months, than did cash only (‘Cash’) or cash and food (‘Cash & Food’) or food only (‘Food’). While these are important findings, as they show that in contexts where MMP are widely available, nutrition BCC interventions can help increase knowledge and awareness of the importance of micronutrients and that this can result in higher consumption of said MMP, the study exhibits the same pitfall that many other attempts to measure the impact of CCT on child health outcomes fall into: the inability to categorically attribute difference purely to conditionality.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In the case of the trials ( 7 ) conducted in the study published in a recent issue of Public Health Nutrition ( PHN ), the results showed that cash conditional on nutrition behaviour change communication (‘Cash + BCC’) yielded higher impacts in terms of knowledge of Fe deficiency, awareness of multiple-micronutrient powders (MMP) and reported consumption thereof for children aged 6–59 months, than did cash only (‘Cash’) or cash and food (‘Cash & Food’) or food only (‘Food’). While these are important findings, as they show that in contexts where MMP are widely available, nutrition BCC interventions can help increase knowledge and awareness of the importance of micronutrients and that this can result in higher consumption of said MMP, the study exhibits the same pitfall that many other attempts to measure the impact of CCT on child health outcomes fall into: the inability to categorically attribute difference purely to conditionality.…”
mentioning
confidence: 99%
“…Unlike other studies that have attempted to measure the impact of conditionality on child health outcomes, the PHN study ( 7 ) looked at knowledge and reported consumption of MMP only and did not measure any objective nutritional clinical outcomes such as anaemia. While it could be argued that once the efficacy of MMP in reducing anaemia has been proven, strategies to increase uptake, such as the ones discussed in the article, will be useful, the lack of objective nutritional clinical outcomes is an important limitation because it leaves us no nearer to answering the question of what impact CCT have on outcomes such as micronutrient deficiency.…”
mentioning
confidence: 99%
See 3 more Smart Citations